The Comparison Of Effectiveness Between Ginger Drinks And Dark Chocolateindecreasingdysmenorrhea - Paramitha Amelia Kusumawardani; Cholifah Cholifah (Universitas 'Aisyiyah Yogyakarta, 2020)
The aims of the study are to measure and obtain data change on dysmenorrhea in the group of ginger drinks and dark chocolateand to compare the effectiveness between ginger drinks and dark chocolate in decreasing dysmenorrhea. Dysmenorrhea disorders can be occur for several hours even up to several days and interfere daily activities. Approximately 15% during menstrual dysmenorrhea has an impact on daily activities, requiring antianalgesic drugs and nearly 40% of dysmenorrhea may require medical treatment and 8-10% are not attending school. The research design uses Quasi Experimental with one group pretest-posttest design. The result ofdifference between pretest and posttest valueobtained by using Paired Sample Test.The result of the research shows the correlation between intensity of dysmenorrhea and ginger drinks seen from significant value α 0.020 α 0.05 while the strength of the relation is medium which seen from correlation strength is 0.592. Whereas there is no correlation between intensity of dysmenorrhea and dark chocolate seen from significant value α 0.421 α 0.05 with low relation strength seen from correlation strength value 0,225. Based on the results, the researchers concluded that ginger drinks is more influential in decreasing dysmenorrhea than dark chocolate with α 0.020 α 0.05.